(untitled) (Taqdir, 2025)
This study aims to analyze the factors that influence the speaking skills (maharah kalam) of Arabic Language Education students at the State Islamic University of North Sumatra, Class of 2023, as well as to determine their level of speaking proficiency. The research employed a descriptive qualitative method with a field research approach through observation, interviews, and documentation. The results indicate that the students’ speaking skills are still relatively low, as evidenced by difficulties in constructing sentences, limited vocabulary, inaccurate pronunciation, and low fluency. Internal factors include limited vocabulary mastery, insufficient understanding of grammatical rules, speaking anxiety, low motivation, and lack of self-confidence. External factors include diverse educational backgrounds, a lack of Arabic-speaking environments, and limited opportunities for practice outside the classroom. This study is based on the behaviorism theory, which emphasizes the formation of language habits through repeated stimulus and response. The application of communicative, audiolingual, and project-based learning strategies is recommended to enhance students’ speaking skills.